The Effectiveness of a Six-Dimensional Strategy in Developing the Skills of Analyzing the Historical Event among Secondary School Students - Emran, Dr. Abeer Mousa (Researchparks Publishing, 2023)
The study aimed to identify the effectiveness of a six-dimensional strategy in developing the skills of analyzing the historical event among secondary school students. The study subjects were intentionally selected from Dar Al-Salam School affiliated to the Marka District Education Directorate in the capital, Amman, during the academic year (2021/2022). The study members were randomly distributed to an experimental group and a control group, with (22) female students in each group. The study tool was prepared, which is: a test in the skills of analyzing the historical event. The researcher verified the validity and reliability of the test. The results showed that there were statistically significant differences between the average scores of female students of the study sample for the control and experimental groups on the test of the skills of analyzing the historical event in the post-measurement and in favor of the experimental group, which indicates the effectiveness A six-dimensional strategy in developing the skills of analyzing the historical event among secondary school students. In the light of the results, the study recommended the need to employ a six-dimensional strategy in the subject of teaching history for the secondary stage.